A rapid technique for screening banana cultivars for resistance to Xanthomonas wilt - Tripathi, L.; Odipio, J.; Tripathi, J.N.; Tusiime, Geoffrey (Springer, 2008)
The banana Xanthomonas wilt disease (BXW) has threatened the livelihood of millions of farmers in East Africa. Use of resistant varieties is the most cost-effective method of managing this bacterial disease. A reliable and rapid screening method is needed to select resistant banana varieties. An in vitro screening method was developed for early evaluation of Xanthomonas wilt resistance using small tissue culture-grown plantlets. Eight cultivars of banana were screened with sixteen isolates of Xanthomonas campestris pv. musacearum using this method. There were significant differences (P < 0.0001) in susceptibility among the various banana cultivars tested, whereas no significant difference (P = 0.92) in pathogenicity was observed between the pathogen isolates. The cv. Pisang Awak (Kayinja) was found to be highly susceptible and Musa balbisiana resistant. Nakitembe was found to be moderately resistant while cvs Mpologoma, Mbwazirume, Sukali Ndiizi, FHIA-17 and FHIA-25 were susceptible. The susceptibility of these cultivars was further tested in vivo by artificial inoculation of potted plants with similar results. This study shows that an in vitro screening test can serve as a convenient, cheap and rapid screening technique to discriminate BXW-resistant from BXW-susceptible banana cultivars.